IMPLEMENTASI PENGGUNAAN E-FORM PADA PELAPORAN SPT TAHUNAN DI KANTOR KONSULTAN PAJAK (RIA TAX CONSULTANT) - Agus Ariana, I Komang; Sari Putri, Luh Putu Rina (Adi Widya : Jurnal Pengabdian Masyarakat, 2023)
In order to encourage taxpayer compliance, the Directorate General of Taxes issued a tax administration system that utilizes technology, namely e-Form. This study aims to obtain evidence regarding the implementation of the use of e-Form in reporting Individual Taxpayer Annual Tax Returns. The analysis method used in this study is an empirical analysis method by obtaining information by collecting data. The results of this study show that the implementation of the use of e-Form in reporting individual taxpayer tax returns at the Ni Made Rianingsih Consultant Office provides many conveniences for taxpayers. The implementation of e-Form as a new breakthrough is expected to be able to provide excellent service to the community so that it can increase state tax revenue optimally.